Implementasi Penghapusan Aset Daerah Tanah dan Gedung di Badan Pengelolaan Keuangan dan Aset Daerah Kota Bandar Lampung - Rizani, Agnessa Shalsabila; Utoyo, Bambang; Faedlulloh, Dodi (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
This study aims to analyze the implementation of asset deletion policies for land and buildings owned by the local government at the Regional Financial and Asset Management Agency (BPKAD) of Bandar Lampung City. The analysis uses the Van Meter and Van Horn policy implementation model, which includes six key variables: policy standards and objectives, resources, inter-organizational communication, characteristics of implementing agents, external environment, and the disposition of implementers. The findings indicate that the policy implementation has not been optimal. Major obstacles include limited human and financial resources, weak inter-agency coordination, uncertified assets, and passive attitudes of implementers. To address these challenges, it is recommended to improve HR capacity and budget allocation, strengthen inter-agency coordination, and accelerate the certification of land assets.